2017
DOI: 10.1111/all.13189
|View full text |Cite
|
Sign up to set email alerts
|

Topical corticosteroid phobia in atopic dermatitis: International feasibility study of the TOPICOP score

Abstract: The TOPICOP score can be feasibly applied across countries and may therefore be useful for obtaining qualitative and quantitative data from international studies and for adapting patient education and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 19 publications
3
67
1
1
Order By: Relevance
“…Another limitation is that this Dutch translation of the Topicop is not validated. However, this does not seem to have influenced our findings since the mean Topicop sum score of parents in the current study was similar to Stadler . Furthermore, we used the questionnaire to compare groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that this Dutch translation of the Topicop is not validated. However, this does not seem to have influenced our findings since the mean Topicop sum score of parents in the current study was similar to Stadler . Furthermore, we used the questionnaire to compare groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Taiwan, the effectiveness of wet‐wrap therapy may be limited because of the humid climate of the country . Treatment in Taiwan and other countries may also be influenced by steroid phobia among patients . In India, it is suggested that in warmer months, patients be kept cool using air conditioning or fans (when air conditioning is not feasible).…”
Section: Managementmentioning
confidence: 99%
“…46 Treatment in Taiwan and other countries may also be influenced by steroid phobia among patients. 52 In India, it is suggested that in warmer months, patients be kept cool using air conditioning or fans (when air conditioning is not feasible). It is also suggested that ear piercing be delayed in children until they are at least 8 years old.…”
Section: Managementmentioning
confidence: 99%
“…The TOPICOP is able to assess various degrees of steroid anxiety in routine clinical practice. We translated the scale into Japanese and reported the feasibility in 2015, and Stalder et al reported feasibility in 2017 based on an international feasibility study of TOPICOP conducted in 15 countries including Japan . The current study was additional analysis by using a part of Japanese data of the feasibility study.…”
Section: Introductionmentioning
confidence: 99%